Knowledge to Practice in Developmental Coordination Disorder: Impact of an Evidence-Based Online Module on Physical Therapists' Self-Reported Knowledge, Skills, and Practice. (1st May 2015) - Camden, Chantal; Rivard, Lisa; Pollock, Nancy; Missiuna, Cheryl
ABSTRACT Aims: To evaluate the impact of an evidence-based online module on Developmental Coordination Disorder (DCD) on self-reported physical therapist (PT) knowledge, skills, and practice. Methods: Fifty PTs completed a questionnaire before and after the completion of the online module, with 41 PTs completing the same questionnaire 2 months later. The questionnaires included items rated using a 7-point Likert Scale and short open-ended questions. Results: There was a significant effect of Time for 17 out of 18 items on self-reported knowledge, and all 19 items for self-reported skills. Post-hoc analyses indicated that mean scores at Time 2 and Time 3 were higher than the mean scores at Time 1. Forty-six (92%) participants reported an increase in their confidence to provide evidence-based services. Forty-three (86%) participants indicated their intentions to modify their evaluative practices (e.g., involving children in goal setting) and their management of DCD (e.g., using the best practice principles, providing resources to families). At the 2-month follow-up, 19 (46%) participants had returned to the module to review information (e.g., video, resources) or to download handouts. Conclusions: The online DCD module appears to be an effective knowledge translation strategy to increase PTs' self-reported knowledge and skills, and to support evidence-informed practice.